Achieving a high-performance, self-powered, broadband perovskite photodetector employing MAPbI3 microcrystal films. Issue 6 (8th January 2020) - Pan, Xiyan; Zhou, Hai; Liu, Ronghuan; Wu, Dingjun; Song, Zehao; Tang, Xiaoming; Yang, Xiaohan; Wang, Hao
Abstract : High-performance, self-powered, broadband MAPbI3 perovskite microcrystal photodetector. Abstract : Organic–inorganic metal halide perovskites have achieved great success in applications such as light-emitting diodes, photodetectors (PDs) and solar cells due to their high light absorption coefficients, tunable band gaps and simple solution-process technologies. However, their polycrystalline films have low carrier mobility and high defect states, which limit the device performance. As substitutes, perovskite microcrystal (MC) films exhibit higher carrier mobility and lower defect state density and thus, they have received much attention in recent years. Herein, we introduce MAPbX3 (X = Br, I) MC films with controllable thickness and adjustable band gap, and the self-powered MAPbI3 perovskite MC PDs (MCPDs) with a structure of ITO glass/perovskite MC film/carbon have been assembled for the first time. By optimizing the thickness of the MC film, our hole-transport-layer-free (HTL-free) PDs exhibit excellent self-powered performance, with an on/off ratio as high as 2 × 10 5, the rise/fall time of 80/580 μs, the responsivity of 0.26 A W −1, the detectivity of 7.01 × 10 11 Jones and the linear dynamic range of 107 dB. In addition, our MCPDs without encapsulation show excellent light and storage stability. These results indicate a good method for preparing high-performance and high-stability perovskite MC devices.